2004
DOI: 10.1103/physrevb.69.233302
|View full text |Cite
|
Sign up to set email alerts
|

Coupled mode of the coherent optical phonon and excitonic quantum beat in GaAs∕AlAs multiple quantum wells

Abstract: We report on the time-resolved study of the coherent coupled oscillation of excitonic quantum beats and GaAs-like longitudinal optical (LO) phonons in GaAs/AlAs multiple quantum wells. The time-domain signals in GaAs/AlAs multiple quantum wells observed by using a reflection-type pump-probe technique show the coherent coupled oscillation with fast dephasing time and the long-lived coherent GaAs-like LO phonon oscillation. Under the condition that the splitting energy of the heavy-hole and light-hole excitons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Coherent exciton oscillations, such as quantum beats and Bloch oscillations, have been extensively studied to understand the ultrafast exciton dynamics 1 2 3 4 5 6 7 8 9 , the interaction of excitons with phonons 10 11 12 13 14 15 16 17 18 , the determination of the splitting energies in inhomogeneous systems 19 20 21 , and applications of ultrafast devices 22 23 24 . However, one problem has been the difficulty of generating a clear and long-lived oscillation.…”
mentioning
confidence: 99%
“…Coherent exciton oscillations, such as quantum beats and Bloch oscillations, have been extensively studied to understand the ultrafast exciton dynamics 1 2 3 4 5 6 7 8 9 , the interaction of excitons with phonons 10 11 12 13 14 15 16 17 18 , the determination of the splitting energies in inhomogeneous systems 19 20 21 , and applications of ultrafast devices 22 23 24 . However, one problem has been the difficulty of generating a clear and long-lived oscillation.…”
mentioning
confidence: 99%
“…This leads to the enhancement of the coherent LO phonon by coupling with the excitonic QB; namely, the QB acts as a driving force for the coherent LO phonon under the resonant condition. It should be noted that the coupled mode of the excitonic QB and coherent LO phonon are clearly observed as appearance of an anticrossing behavior in the HH-LH-splitting-energy dependence of the FT bands in initial time domain signals [3]. It is well known that the appearance of the anticrossing behavior is a direct evidence for the existence of the coupled mode: One of typical examples is a plasmon-LO-phonon coupled mode.…”
Section: Methodsmentioning
confidence: 96%
“…In our previous works with a pump-probe technique [2][3][4][5], we demonstrated that the excitonic QB couples with the coherent longitudinal optical (LO) phonon under the energy resonance condition of the QB and LO phonon in GaAs/AlAs multiple quantum wells (MQWs), which leads to considerable enhancement of the coherent LO phonon. The physical mechanism for the enhancement is attributed to the resonant polarization coupling between the QB and coherent LO phonon; namely, the coherent LO phonon is driven by the QB.…”
mentioning
confidence: 99%
“…3,4 Variations of the optical phase between the pulse pairs in a controlled 3 or statistical way (COIN) 5 have been investigated. In the condensed environment, the method has been introduced besides other techniques 6,7 to study predominantly electronic coherence in photoemission from surfaces, 8 excitons in semiconductors 9 and site effects in molecular crystals. 10 In this contribution, we emphasize the original idea to study coherence properties of vibrational wavepackets in electronically excited states and we chose Cl 2 in an Ar matrix as the analogous system of a dihalogen in a crystalline rare gas environment.…”
Section: Introductionmentioning
confidence: 99%